2000
DOI: 10.1006/asle.2000.0018
|View full text |Cite
|
Sign up to set email alerts
|

Report of RMS Discussion Meeting 21 June 2000: “Some aspects of the general circulation of the atmosphere” ‐ Presidential Address

Abstract: Abstract:The extent to which the North Atlantic Oscillation (NAO) is in¯uenced by changes in the ocean state is an issue that has attracted much recent attention. Although there have been counter claims, the weight of evidence clearly suggests that forcing by the ocean of year-to-year changes in the NAO is a weak in¯uence by comparison with atmospheric internal variability. The NAO is thus very different in character to the Southern Oscillation (SO), and its predictabilityÐat least on seasonal-to-interannual t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
76
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(82 citation statements)
references
References 33 publications
6
76
0
Order By: Relevance
“…In support of the mechanisms proposed in sections 3.2 and 3.3, many AGCM studies suggest a positive feedback between the SST tripole as a whole and the NAO [Venzke et al, 1999;Rodwell et al, 1999;Watanabe and Kimoto, 2000b;Cassou and Terray, 2001a;Sutton et al, 2001;Terray and Cassou, submitted;Peng et al, 2002], although not all [Robertson, 2001]. Analysis of the observational record should thus at least provide a hint for such a feedback.…”
Section: Sst Impact On Nao In Observationsmentioning
confidence: 69%
See 2 more Smart Citations
“…In support of the mechanisms proposed in sections 3.2 and 3.3, many AGCM studies suggest a positive feedback between the SST tripole as a whole and the NAO [Venzke et al, 1999;Rodwell et al, 1999;Watanabe and Kimoto, 2000b;Cassou and Terray, 2001a;Sutton et al, 2001;Terray and Cassou, submitted;Peng et al, 2002], although not all [Robertson, 2001]. Analysis of the observational record should thus at least provide a hint for such a feedback.…”
Section: Sst Impact On Nao In Observationsmentioning
confidence: 69%
“…It is worth emphasizing that aquaplanet GCMs typically lack such interactions [e.g., Ting, 1991], and even GCMs with zonal asymmetries do not systematically produce equivalent barotropic structures in response to middle latitude SST anomalies [Kushnir and Held, 1996]. Accordingly, predicted atmospheric responses to an anomalous meridional SST gradient along 45ºN can vary between AGCMs, although a strengthening of the westerlies in response to a strengthening of the meridional SST gradient along 45ºN appears to be robust [e.g., Watanabe and Kimoto, 200b;Sutton et al, 2001;Peng et al, 2002]. This is consistent with a positive feedback on the NAO from the extra-tropical part of the SST tripole, but model studies suggest the feedback amplitude is weak compared to intrinsic variability.…”
Section: Mechanisms Of Sst Feedback In Middle Latitudesmentioning
confidence: 99%
See 1 more Smart Citation
“…On decadal time scales, observational studies suggest that SST variability may be correlated over the whole Atlantic basin from the South Atlantic to Greenland (Xie and Tanimoto 1998;Rajagopalan et al 1998;Tourre et al 1999;Tanimoto and Xie 1999). During boreal winterspring seasons, as part of this so-called panAtlantic decadal oscillation (PADO), the tropical dipole, with a strong cross-equatorial SST gradient that forces the ITCZ to move in the meridional direction, is apparently involved in a two-way tropical-extratropical interaction with the NAO (North Atlantic Oscillation) as model studies suggest (Xie and Tanimoto 1998;Okumura et al 2001;Sutton et al 2001). When a northward cross-equatorial SST gradient occurs, sea level pressure (SLP) anomaly field shows a southward gradient, whose centers of action are displaced poleward of maximum tropical SSTAs and found at 30 (Tanimoto and Xie 1999).…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that analysis of North Atlantic climate variability must take into account the role of the whole Tropics, including both Pacific and Indian Ocean sectors Hurrell et al, 2004). On the other hand, the SSTA in March and April that correlates with rainfall in May, suggest a strengthening of the westerlies in response to a strengthening of the meridional SST gradients that has been seen in wintertime (Sutton et al, 2001).…”
Section: Discussionmentioning
confidence: 99%